THE EFFECT OF ROLLING CYCLES AND SETTING DIRECTION OF THE REINFORCEMENT ON ALUMINUM BASED COMPOSITE BY REPETITIVE PRESS ROLL FORMING (RPRF) METHODS - Agus Pramono; Tri Alif Shandy; Yeni Muriani Zulaida; Suryana Suryana; Moh Fawaid (VANOS Journal of Mechanical Engineering Education, 2018)
Development of technology shown rapid progress in various of structural applications especially on advanced of component in industry. Using of aluminum as a matrix on composite fabrication by addition ceramic as reinforcement is the better solution, for expected to improve the mechanical properties on materials-based composites. The process carried out was combining SiC particles with an aluminum (AA1100) as a matrix with variations number of rolling cycle’s: 2, 4 and 6 as direction. Preparation of SiC particles with transverse, cross section and mix variations through a hot working process with the technology of severe plastic deformation (SPD) using the method of repetitive press roll forming (RPRF). The results obtained was mechanical properties increased when the roll cycles high with mix of variations in the direction of SiC arrangement resulting in a wider distribution of SiC into the matrix AA1100. Rolled process by cycle 6 and the direction of the SiC mix resulted in higher hardness of 55.54 HV, tensile strength was 90.46 MPa, porosity 0.33% density 1.831 gr/cm3 and SiC distribution 23.19%. Increasing the number of rolling cycles, the thickness of the interface for the formed layer and the size of SiC particles will decrease due to SiC particles scattered in most aluminum matrices, which can increase the hardness value.